Exploring the role of agile governance in responding to the COVID-19 pandemic in Indonesia: a literature review - Oscar Radyan Danar (Publisia: Jurnal Ilmu Administrasi Publik, 2023)
The COVID-19 pandemic has brought many alterations to the government’s policy structures due to its multidimensional impact. To minimize the impact, governments need to adopt the agile governance method as a principle enabling organizations to respond and adapt quickly toward unexpected changes under uncertain conditions. This study goals to report of systematic review about government policies in managing the COVID-19 pandemic in Indonesia through an agile governance perspective. The research method applied in this study is a systematic literature review of a set of current literature articles emanating from the idea of agile governance for managing the pandemic. The results of this study were formulated through a peer review of the article synthesis according to the six principles of agile governance to determine the resulting distribution. The research results show that the application of agile governance in Indonesia can reduce the negative impact of the COVID-19 pandemic through various policies set by the government, although several principles and policies are not implemented efficiently. However, the agile and adaptive principles promoted by the principles of agile governance enable the government to make adaptive decisions and policies in uncertain situations.